Living Qur’an Dalam Tradisi Yasinan Di Masyarakat Desa Wonosari Kabupaten Bengkalis - Riyaldi, Rino; Muslim, Muslim; M. Kafrawi (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2025)
In Indonesian society, a tradition represents a social response as a form of appreciation for the presence of the Qur'an. One such tradition that has endured to this day is Yasinan. Yasinan is a form of cultural acculturation practiced by Muslims in Indonesia for generations. This tradition can be found in various regions, particularly rural areas or villages. This research is a field study using a qualitative descriptive approach. Data collection techniques include observation, interviews, and documentation studies. The findings reveal several forms of Surah Yasin recitation practices in Wonosari Village, namely: (1) Yasin on Friday nights, (2) Yasin during the throes of death, (3) Yasin after someone's passing, (4) Yasin as a form of healing, (5) Yasin on the night of Nisfu Sya’ban, and (6) Yasin to fulfill specific needs. This study also highlights how the Yasinan tradition is not merely a religious ritual but also a mechanism for social and cultural adaptation in the face of changing times. These findings contribute new insights into understanding the role of the Qur'an as a living tradition that continues to evolve and influence the socio-cultural life of Indonesian Muslim communities, particularly at the local level